Pre-primary teachers’ preparedness in integrating information and communication technology in teaching and learning in Tanzania - Tandika, Pambas Basil; Ndijuye, Laurent Gabriel (Information and learning science, 2019)
Purpose Integration and use of technology in teaching and learning in the education sector from pre-primary education (PPE) to the higher levels of education, is a policy issue. In developed countries, including Tanzania, information and communication technology (ICT), especially in PPE, is inadequately researched for laying evidence on its applicability in instruction and learning. Therefore, this paper aims to determine pre-primary teachers’ preparedness in integrating ICT in classroom instruction and challenges teachers face in integrating it for child’s meaningful learning. Design/methodology/approach Methods and instruments: a qualitative transcendental phenomenological approach was used in determining teachers’ preparedness in integrating ICT in PPE in Tanzania. It was further used to collect data that describe the teaching and learning through the integration of ICT in every session as their lived experience for pre-primary teachers. Its selection was appropriate as it allowed researchers to systematically analyse for description the commonalities and differences existing among the involved teachers in integrating ICT in teaching and learning as their lived experiences (Moerer-Urdahl and Creswell, 2004). To appropriately analyse teachers’ understanding and experiences regarding ICT and its integration in teaching and learning in pre-primary classes, semi-structured interviews and open-ended questionnaires were used for in-depth understanding of the study problem. Semi-structured interviews were used to collect data through open-ended questions where researchers took an average of 40 min per session with participants’ (teachers) using notebooks to take note of their thoughts, feelings and beliefs about ICT integration in PPE. Use of the semi-structured interview was based on the reality that it provides in-depth information pertaining to participants’ experiences and viewpoints of a particular topic (Turner, 2010). Once the interview session was complete, each teacher was given a questionnaire to fill in for triangulating their experiences. Description of participants: a total of 14 schools constituting 28 teachers were purposively sampled and engaged in this study. Analysis of participants’ demographic characteristics indicates that all of the involved teachers had certificate in teacher education that qualified them as primary school teachers. Meanwhile, 18 (66.7 per cent) of the pre-primary school teachers who were involved in this study were female with only 10 (33.3 per cent) had working experience at and above five years of teaching in early grade classes. Study participants (teachers) from Itilima and Meatu Districts were purposively involved in the study as their experiences in young children’s learning and contextual influences (educational and training policy of 2014, the ICT policy of 2007, and foreign studies) are potential in improving the quality of learning. Study area: the current study was conducted in two districts (Itilima and Meatu) all found in Simiyu region. The two districts were selected and considered appropriate by the study as they constituted the 17 most disadvantaged rural areas in Tanzania (Mosha et al., 2015). Authors describe the two districts as having poor educational outcomes mainly relatively low pass rates in the primary school leaving examination results. In Itilima, one ward out of 22 was studied in which its six schools [with a total of 12 teachers] among 87 schools in the district were involved. While in Meatu district, eight of 121 schools [with a total of 16 teachers] in one ward of 29 wards were studied. This implies that a total of 14 schools and 28 teachers were involved in this study. Data analysis: the data collected through the interviews and open-ended questionnaires were subjected to content analysis procedures (reading and re-reading notes and transcripts followed by a three-steps-coding process consisting of open, axial and selective coding procedures). The analysis process was informed by the Vagle’s (2014) six steps for phenomenological research data analysis procedure (holistic reading of the entire text, first line-by-line reading, follow up questions, second line-by-line reading, third line-by-line reading, and subsequent readings). Practically, the researchers read and re-read the texts and transcribed data from the language used during data collection that is Kiswahili, into the reporting language that is English. Following transcription, data were coded for developing categories of data through axial and elective coding processes. Findings The data analysis was conducted and results and its discussion are presented in three sub-sections: preparedness of teachers in using ICT in teaching and learning; teachers’ views about the integration of ICT in teaching and learning; and challenges faced by teachers in integrating ICT in teaching and learning. Teacher’s preparedness in the use of ICT in teaching: exploration of teachers’ preparedness in integrating ICT in teaching and learning was preceded by exploration of teachers’ understanding of ICT in teaching and learning. Analysis revealed that majority of teachers were aware about ICT in teaching and learning and they understood it as the implementation of curriculum at school level that involves use of ICT-based facilities such as television, mobile phones, computer and radio. Teacher elaborated that appropriate use of ICT-based facilities that would later develop children to potentially improve their understanding and practical application in daily life. Other teachers understood ICT in teaching and learning as use of printed materials [newspapers and magazines] in facilitating pupil’s learning of planned lessons. While other teachers were aware of what ICT means the second category of teachers as noted in their responses, had limited understanding, as to them, ICT in education meant use of printed materials. Difference in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as use of ICT facilities in developing children’s competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Their views are based on the development of children with competencies useful in facilitating further learning in the subject known as Teknolojia ya Habari na Mawasiliano. Following the question based on exploring teachers’ understanding of ICT in teaching and learning, researchers explored teachers’ preparedness in using ICT in teaching and learning. Table 1.0 illustrates teachers’ multiple responses regarding their preparation. Table I: teacher’s preparedness in using ICT in teaching and learning. S/N; preparedness; freq; and per cent. Enhancing child’s understanding on the use of ICT-based facilities-20, 71.4; using remedial sessions teaching ICT-12, 42.8; using ICT-based facilities for teaching other classes-8, 28.5. Table 1.0 illustrates that teachers are prepared to enable children use ICT to access information and more knowledge related to their school subjects and general life. They were of the view that ICT could serve well in areas where text and supplementary books are scares or torn-out by pupils because were poorly bound or due to poor quality of papers used. Therefore, availability of ICT facilities in schools would become important resource-materials for pupils, as well as teachers. For instance, a teacher said that; Availability of ICT facilities, such as computers in schools will help us in preparing notes or content for supplementing their learning. Different from the paper-based notes, computers will keep our notes properly compared to the papers that get easily displaced and hard to retrieve notes when lost (Interview, 20 April 2016). In addition to the use of ICT facilities in serving as resource material, their use in schools would aid pupils and teachers to use them beyond teaching and learning. Teachers narrated that children may find games and puzzles that all help in stimulating their thinking, hence interest in schooling and further learning. Teachers also said they are prepared to use even extra hours that are beyond school timetable to ensure children learn well to meet the uncovered periods once facilities are placed in school. Use of extra hours beyond the normal school timetable comm. Research limitations/implications The study was limited to the accessed and involved schools as some schools were found to have no specific teachers teaching a pre-primary class on reasons the responsible teacher for the class had retired. As a result, researchers spend extended time to travel and reach schools that were located far from one school to the other. Again, some teachers were reluctant in participation on reasons that researchers are evaluating their competency for reporting to the higher authorities. Practical implications Differences in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as the use of ICT facilities in developing pupils’ competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Effective integration of ICT for efficiency in instruction depends on the teacher’s preparedness especially competency in using the equipments and infrastructures especially electric power. Social implications Integration of Information and Communication Technology in teaching and learning in PPE is socially important in the view that all children regardless of their background (urban or rural, affluent or poor) benefits in learning through use of technology. The children’s access to education integrating ICT would ensure equal opportunities